2020
DOI: 10.1021/acs.jmedchem.9b02011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Inactive-State κ Opioid Receptor Homodimerization via Single-Molecule Microscopy Using New Antagonistic Fluorescent Probes

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 104 publications
0
17
1
Order By: Relevance
“…Indeed, the group of Decker showed that by tagging GNTI at the 5’‐position with sulfo‐Cy3 and sulfo‐Cy5 fluorophores, κOR selective fluorescent ligands 94a‐b were obtained (Scheme 53A). However, in this study, they could not detect any dimerization of κORs and the authors suggest that the fluorescent ligands are mostly present as freely diffusing monomers on the surface of transiently transfected CHO cells [193] …”
Section: Fluorescent Ligands For Gpcrscontrasting
confidence: 58%
See 1 more Smart Citation
“…Indeed, the group of Decker showed that by tagging GNTI at the 5’‐position with sulfo‐Cy3 and sulfo‐Cy5 fluorophores, κOR selective fluorescent ligands 94a‐b were obtained (Scheme 53A). However, in this study, they could not detect any dimerization of κORs and the authors suggest that the fluorescent ligands are mostly present as freely diffusing monomers on the surface of transiently transfected CHO cells [193] …”
Section: Fluorescent Ligands For Gpcrscontrasting
confidence: 58%
“…However, in this study, they could not detect any dimerization of kORs and the authors suggest that the fluorescent ligands are mostly present as freely diffusing monomers on the surface of transiently transfected CHO cells. [193] Scheme 52. Opioid receptor ligands and fluorescent ligands.…”
Section: Fluorescent Ligands For Melatonin Receptors (Mtrs)mentioning
confidence: 99%
“…However, for κOR, the yellow fraction increases from a low value of 10% at a density of 14/µm 2 to a high value of 46% for densities of > 100/µm 2 , supporting the expected density dependence of the κOR dimer/cluster fraction. As supported by previous studies on GPCRs and ORs, we assume in the following that the κOR is either monomeric or dimeric [2][3][4][5][6][7][11][12][13][14].…”
Section: Dissociation Constant Of κOrmentioning
confidence: 99%
“…µOR seems to be monomeric when unliganded and switches to a dimeric state when the ligand DAMGO is bound, but interestingly stays monomeric upon binding of morphine [ 11 , 12 ]. κOR has been observed to be primarily monomeric [ 13 ]. However, for these studies, experiments were performed at low densities < 1/µm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…μOR seems to be monomeric when unliganded, but switches to a dimeric state when the ligand DAMGO is bound, but interestingly stays monomeric upon binding of morphine [11, 12]. κOR has been observed to be primarily monomeric [13]. However, for these studies, experiments were performed at low densities < 1 / µm 2 .…”
Section: Introductionmentioning
confidence: 99%